Guns, drugs, and development in Colombia - Holmes, Jennifer S. (University of Texas Press, 2008)
Introduction -- Historical and geographical propensities to violence -- Colombian economic history : regional context and Colombian policies -- The main actors in the 1990s and into the twenty-first century : guerrillas and paramilitaries -- Differences within Colombia and available subnational data -- Guns and protection : guerrillas and paramilitaries -- The effects of illegal drugs and violence on the Colombian economy -- Acknowledging constraints to find comprehensive peace : the four cornerstones of pacification